Sugarcane and Eucalyptus plantation equally limit the movement of two forest-dependent understory bird species - Giubbina, Marina Furlan [UNESP]; Martensen, Alexandre Camargo; Ribeiro, Milton Cezar [UNESP] (Wiley, 2018)
Habitat fragmentation results in landscape configuration, which affects the species that inhabit it. As a consequence, natural habitat is replaced by different anthropogenic plantation types (e.g. pasture, agriculture, forestry plantations and urban areas). Anthropogenic plantations are important for biodiversity maintenance because some species or functional groups can use it as a complementary habitat. However, depending on plantation permeability, it can act as a barrier to the movement of organisms between habitat patches, such as forest fragments, reducing functional connectivity for many species. Anthropogenic plantations are becoming the most common land use and cover type in the Anthropocene and biodiversity conservation in fragmented landscapes requires information on how different plantation types affect the capacity of the species to move through the landscape. In this study, we evaluated the influence of the type and structure of plantations on the movement of two forest-dependent understory bird species – plain antvireo (Dysithamnus mentalis) and flavescent warbler (Myiothlyps flaveola) – within a highly fragmented landscape of Atlantic Forest hotspot. Knowing that forestry plantation is assumed to be more permeable to dependent forest bird species than open ones, we selected six study areas containing a forest fragment and surrounding plantation: three with sugarcane plantation and three with Eucalyptus sp. plantation. We used playback calls to stimulate the birds to leave forest fragments and traverse the plantations. Control trials were also carried out inside the forest fragments to compare the distances crossed. We observed that individuals moved longer distances inside forest than between plantation types, which demonstrate that plantations do constrict the movements of both species. The two plantation types equally impeded the movements of the species, suggesting the opposite of the general assumption that forestry plantations are more permeable. Our results indicate that, for generalist species, plantation type does not matter, but its presence negatively impacts movement of these bird species. We highlight that plantations have negative influences on the movements of common bird species, and discuss why this is important when setting conservation priorities.
Keywords: Atlantic forest; bird movement; Dysithamnus mentalis; Myiothlypis flaveola; plantation permeability